(untitled) (European Journal of Health Research, 2020)
Basic psychological needs theory defends that social contexts which promote basic psychological needs for autonomy, competence and relatedness, have a positive effect on people’s well-being. Based on this theoretical framework, the aim of this study was to analyze the possible relationships between older people’s perceived social support, their basic psychological needs satisfaction and their well-being, measured by life satisfaction and selfesteem. Participants of the study were 137 older people. Results of the study showed that both perceived social support and basic psychological needs satisfaction act as positive and significant predictors of elderly people’s well-being. Finally, results revealed that basic psychological needs satisfaction functions as a mediator in the relationship between perceived social support and older people’s life satisfaction. This mediational role couldn’t be demonstrated in the relationship between perceived social support and self-esteem. These results emphasize the importance of developing programs that promote an adequate social support and the basic psychological needs satisfaction of the elderly people to promote their well-being.